Variasi Akronim Bahasa Indonesia dalam Bahasa Gaul Remaja di Media Sosial Tiktok - Ifani, Yulia; Liusti, Siti Ainim (Persona: Kajian Bahasa dan Sastra, 2024)
This study aims to explain two main points of discussion, namely (1) the form and pattern of formation of Indonesian acronym variations in teen slang on Tiktok social media and (2) the meaning of Indonesian acronym variations in teen slang on Tiktok social media. This type of research uses qualitative research with descriptive methods. The data in this study were obtained from the posts of the Tiktok accounts that have been determined, namely the @Lyodra Ginting, @Fujiian and @Nabila Taqiyyah accounts, which were taken from the captions and comment columns of posts throughout 2023 (January-December 2023). The method used in data collection is descriptive method, which is research conducted without numbers but obtained in the form of description data in the form of vocabulary, but the data is first taken by copying and pasting the data. The result of the research shows that (1) there are 85 data of forms and patterns of formation and their meanings included in Kridalaksana's theory, and (2) there are 9 data of the addition of new forms and patterns of formation in acronym variations in teen slang.